Stereoisomers resulting from the hindered rotation in N-(o-ARYL)-2,4-oxazolidinedione derivatives - Ordu, Öznur Demir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2001., 2001)
In this study, sterically hindered 5-methyl-3-(o-aryl)-2,4-oxazolidinediones and 5,5-dimethyl-3-(o-aryl)-2,4-oxazolidinediones have been synthesized by the reaction of the o-aryl isocyanates with (S)-(-)-ethyllactate or ethyl á-hydroxyisobutyrate, respectively.Diastereomeric isomers of the 5-methyl-3-(o-aryl)-2,4-oxazolidinediones have been detected by using 1 H NMR. Enantiomeric isomers of the 5,5-dimethyl-3-(o-aryl)-2,4-oxazolidinediones have been identified by 1 H NMR and 13 C NMR, also in the presence of the chiral auxiliary. Activation barriers to hindered rotation around C-N single bond have been determined for o-methyl and o-chloro substituted enantiomers by using DNMR. The conformational preferences of the diastereomers have been investigated by 1 H NMR and by HPLC on an optically active sorbent. The rotation in the o-fluoro derivatives was found to be too fast to make the rotational isomers observable by NMR, whereas the rotational isomers of the ortho bromo compounds were found to be separable at room temparature. Using HPLC on cellulose carbamate the isomers were separated and for the diastereomeric isomers of 5-methyl-3-(o-bromophenyl)-2,4-oxazolidinedione, the equilibrium constant and the energy barrier for the conversion of the less stable conformation to the more stable one were determined by following the equilibration of the isomers at constant temperature.In addition, the reactions of halogen substituted 5-methyl-3-(o-aryl)-2,4-oxazolidinediones with methanol have been studied. The compounds were found to react with methanol, causing a ring opening reaction. The products were identified by 1H NMR.
Keywords: Isomerism.